O discurso do protagonismo juvenil: uma análise da implementação do novo ensino médio no Amazonas a partir da Lei n° 13.415/17 - Farias, Ester Sara da Silva (Brasil, 2025)
In the inaugural lecture at the Collège de France, given on December 2, 1970 and later entitled “The Order of Discourse” (2012), Foucault states that, in every society, discourse is produced and made as a “truth”, that is, a “knowledge” socially constructed through “power” relations, which may prevail over time. In this context, a knowledge constructed about young people, previously seen as delinquents, but who today, on the other hand, are seen as protagonists in the resolution of social, political and even economic problems. This, of course, comes from this socially constructed knowledge about them, which ends up reflecting on the way in which Educational Policies are constructed from this perspective. Based on this notion, the objective of this research is to analyze the sayings, that is, the sets of statements that make up the discourse of “youth protagonism” and how it has been produced in the context of the New High School Reform in Amazonas, as provided for in Law No. 13,415/2017. Therefore, from this study, which uses as a theoretical-methodological sport the genealogical analysis of discourse inspired by Foucault, that is, starting from a qualitative organization of documents, it was possible to conclude that young people have become objects of actions of the Educational Policy, through a discourse that is subjectivized in such a way that they recognize themselves as individuals capable of promoting social, political and economic transformations, thanks to the empowerment provided mainly by education. Thus, the announced, that is, the small pieces that make up this discourse of youth engagement, are “social actors”, “agents of social change”, “entrepreneurs of themselves” and even “protagonists”, who make up this knowledge formed about young people. This discourse is constructed by different subjects, such as parents, teachers, global cooperation agencies, who begin to dictate the need for a society that is increasingly demanding in relation to skills and abilities, which materializes in the curricular change of the New High School.